Microcystins and cylindrospermopsins molecular markers for the detection of toxic cyanobacteria: a case study of northeastern Brazilian reservoirs - Lorenzi, Adriana Sturion; Chia, Mathias Ahii; Piccin-Santos, Viviane [UNESP]; Bittencourt-Oliveira, Maria do Carmo (Asoc Espan Limnol-mislata, 2015)
The presence of potentially toxic cyanobacteria in 10 northeastern Brazilian reservoirs used for public water supply was evaluated with molecular markers specific to genes of microcystins (MC) and cylindrospermopsins (CYN). The detection of the MC genes mcyA and mcyB was determined using 3 different primer pairs. Genes of CYN were assessed by PCR amplification of PKS and PS genes. Amplicons of the different cyanotoxin genes were subjected to sequencing. Genes coding for MC (mcyA and/or mcyB) were found in all of the analysed samples. Despite the presence of the mcyB gene and the subsequent immunological detection of MC, the absence of mcyA was observed in several samples. In general, the primers targeting the PKS gene were more specific, while those for the PS gene gave uneven PCR amplification. In addition, the detection of CYN was only possible when the samples were positive for both the PKS and the PS genes. These findings show that, when working with environmental samples, the use of molecular markers for the detection of potentially toxic cyanobacteria may generate variable results, and consideration should be given to possible phytogeographic genetic variations.
Keywords: Early warning; genotype composition; peptide synthetase; public water supply; water monitoring